2013
DOI: 10.1002/clen.201200316
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relative Adequacy of Landfills as a Means of Solid Waste Disposal in Malaysia

Abstract: This study examined the relative adequacy of active landfills between states in Malaysia. The percentages of closed landfills were determined. The accessibility and loading of the landfills were examined. The characteristics of each landfill studied were noted. The study involved the compilation and analyses of data on groundwater, stream water and current land use surrounding landfills. Results of the study showed that the number of active landfills was not adequate to handle solid waste disposal. The potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The large number of unaccounted open dumpsites throughout the country has humongous implications for the quality of the soil surrounding the dumpsites. While MSW is properly contained and the leachate is adequately managed in proper landfill facilities, illegal dumpsites lack these pollution control mechanisms to minimize the contamination caused by the MSW therein to their surroundings [9]. Even with some level of management, it has been reported that heavy metals such as Mn, Fe, Ni, Cr, Pb, Zn, Co, and Cu were detected in the soil horizons beneath the waste disposal zone of a landfill [10].…”
Section: Introductionmentioning
confidence: 99%
“…The large number of unaccounted open dumpsites throughout the country has humongous implications for the quality of the soil surrounding the dumpsites. While MSW is properly contained and the leachate is adequately managed in proper landfill facilities, illegal dumpsites lack these pollution control mechanisms to minimize the contamination caused by the MSW therein to their surroundings [9]. Even with some level of management, it has been reported that heavy metals such as Mn, Fe, Ni, Cr, Pb, Zn, Co, and Cu were detected in the soil horizons beneath the waste disposal zone of a landfill [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other causes of contamination are seepage from waste containments and seawater intrusion [11][12][13][14][15] and spills [16][17][18][19] causing changes in the geochemistry of the area and affecting the quality of the water for agricultural and drinking purposes [20,21]. The water needs to be cleaned up through several means of remediation [22][23][24][25] guided by established standards [26].…”
Section: Introductionmentioning
confidence: 99%